POPULATION OF THE OHABA COMMUNE (PANGEEA, 2025)
The last century’s progressive development of cities associated with the expansion of the industrial society, has led to a corresponding decline of the rural areas. Rural space has lost and loses its most important resource, the human resource. Without this critical resource, expressing the value of its riches becomes a difficult to almost impossible task.